Rhetoric in the Islamic-Javanese Communication Pesantren Tradition: An Ethnographic Study of Instructional Communication at the Ngalah Islamic Boarding School, Pasuruan, East Java, Indonesia - A'yun, Zulia Qurota; Prianti, Desi Dwi (Analisis: Jurnal Studi Keislaman, 2024)
This study is rooted in the uniqueness of the pesantren tradition that combines local religious and cultural values in communication practices, which often differ from the concept of Western rhetoric oriented towards ethos, pathos, and logos. In the Ngalah Islamic Boarding School, rhetoric not only functions as a means of communication, but also as a means to build and strengthen spiritual and emotional relationships between the kiai and the students, without ignoring the values of the Ahlus Sunnah Wal Jama'ah tradition. This study uses a descriptive qualitative approach with an ethnographic method, involving observation, documentation, and in-depth interviews with the kiai and students to understand the dynamics of their communication and relationships. Data are processed through data reduction, data presentation, and drawing conclusions. The research findings show that Kiai Sholeh Bahruddin applies an emotional approach through the practice of nyuwuk, which strengthens the bond between the kiai and the students, creating a relationship that goes beyond just teacher and student, to resemble the relationship between father and son. This study also revealed that the rhetoric in this Islamic boarding school functions as a means to build deep spiritual relationships and integrate religious values with general education, as well as making a significant contribution to the formation of character and social integration of students.